2007
DOI: 10.2223/jped.1646
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of retinol levels in human colostrum in two samples collected at an interval of 24 hours

Abstract: Evaluation of retinol levels in human colostrum in two samples collected at an interval of 24 hours Avaliação dos níveis de retinol no colostro humano coletado no intervalo de 24 horas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Procedures were adapted as described by Ribeiro et al. 17 for HM samples. Retinol concentrations ≤0.70 µmol/L in serum and ≤1.05 µmol/L in milk were considered insufficient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Procedures were adapted as described by Ribeiro et al. 17 for HM samples. Retinol concentrations ≤0.70 µmol/L in serum and ≤1.05 µmol/L in milk were considered insufficient.…”
Section: Methodsmentioning
confidence: 99%
“…Retinol concentrations were determined by high performance liquid chromatography (HPLC) according to the procedures for serum samples proposed by Arnaud et al 15 and by Giuliano et al 16 . Procedures were adapted as described by Ribeiro et al 17 for HM samples. Retinol concentrations 0.70 mmol/L in serum and 1.05 mmol/L in milk were considered insufficient.…”
Section: Sample Analysismentioning
confidence: 99%
“…5 lysozyme, and lymphocytes by 60%-75%, whereas freezing at +4 C for 24 hours produces a 40% decrease of many of the same bioactive substances. [10][11][12] Is Lactoferrin Responsible for the Antiinfective Actions of Human Milk?…”
mentioning
confidence: 99%
“…Some studies have suggested that colostrum may be a biochemical indicator of vitamin A status; therefore, breast milk vitamin A can be used for monitoring the impact of vitamin Arelated intervention programs as it is easy to obtain in a non-invasive manner [37,39].…”
Section: Discussionmentioning
confidence: 99%